Highly specific colon-targeted transformable capsules containing indomethacin immediate-release pellets for colon cancers therapy. (2nd January 2020) - Yang, Chen; Zhang, Yu; Cai, Peng; Yuan, Shirui; Ma, Qiaofang; Song, Ya; Wei, Haobo; Wu, Ziheng; Wu, Zhenghong; Qi, Xiaole
Abstract: Generally, definite intestine targeting and immediate drug releasing are both important for the treatment of colon cancer via oral administration of anti-cancer drugs. We developed a highly specific oral colon-targeted pulsatile capsule, based on the effective enzyme-responsive 'pulse plug', which can be degraded under mannanase abundant in colon. Indomethacin (IN) solid dispersion immediate-release pellets were filled in an insoluble capsule body, a guar gum-lactose-hydroxypropyl methylcellulose (HPMC) composed tablet was embedded on the top of capsule as the 'pulse plug', and then covered by enteric soluble cap. In this study, the influence of the proportion of guar gum/lactose/HPMC, the viscosity of HPMC, and the tablet weight on the degradation behaviour of the plug tablet was investigated. The drug-releasing profiles of those pulsatile capsules in different simulated colon medium verified the 'pulse plug' could realise the colon-targeted pulsatile drug-releasing. Furthermore, the rabbit pharmacokinetic experiments showed that the in vivo time lag of drug loaded pulsatile capsules was significantly extended to 5.61 ± 0.08 h ( p <.01), compared with that (0.33 ± 0.47 h) of the marketed tablets (YUNPENG ® ). These results indicated that colon-targeted pulsatile capsules would be effective oral delivering system for colon cancers therapy.